Koli women wearing Nauvari sarees - Mumbai Archive Project Team (Jio Institute, 2024)
During Narali Purnima, Koli women wear ornate versions of the Nauvari saree, often made of silk with motifs such as paisleys, peacocks, and other floral designs. Richly decorated borders and pallus (the end part of the saree) add to the elegance and aesthetic appeal of the Nauvari saree.